(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
The research clarifies the role of Shura Council in the Wilayat of Damascus, or until the reign of Ibrahim Pasha for many years, and in its role in the formation of the State Council, where Prince Bashir al-Shihabi was assigned to form this Council in 1832, and the members of the Council were selected from all the people of Syria. The mission of the council was to judge people according to the rules of legitimacy and the need to abide by fairness, justice and the realization of truth. In addition, it discussed the mechanism of the work of the Council in terms of the issuance and registration and seal of records. There were sometimes cases addressed directly to Mohamed Hali Pasha in Egypt, who was following the conditions of the ruling himself and urges to prevent injustice and fairness to the oppressed. After the withdrawal of Egyptian forces from Damascus, the new advisory board was formed and the powers of the state council were limited to discussing the internal affairs of the state. The meeting also discussed the mechanism of working in the council, where the holiday was on Friday, in addition to holidays and occasions. The council’s duties included supervising markets, combating high prices, appointing Aghawat for the eight sections of Damascus, and urgent cases.